Web-Based Dashboard for Monitoring Penetration Testing Activities Based on OWASP Standards - Yansyah Saputra Wijaya; Imaniar Ramadhani (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2020)
Financial Services Authority Regulation concerning Application of Risk Management in the Use of Information Technology by Commercial Banks which requires Banks to ensure information security to maintain which must be done periodically at least once a year. The most popular way to have security is through pentest, to determine an application whether it is safe and successfully passed the pentest, we need a measurement standard, specifically for web applications, the standard commonly used is OWASP. However, OWASP has a very large list of vulnerabilities, so to simplify the process of monitoring the pentest process in an organization we need a tool that can visualize existing vulnerabilities from various applications to be more easily measured, calculated, and monitored during the pentest process. The tool commonly used to present information to managers is a Dashboard. The dashboard produced in this research is the monitoring dashboard of pentest monitoring activities, it is made using the PHP programming language so that it is web-based and uses the OWASP standard until 2017. The system is also capable of displaying application vulnerabilities based on their frequency of appearance.